The prognostic difference study on the individualized clopidogrel administration in Hmong and Dong patients based on the CYP2C19 gene polymorphism after percutaneous coronary intervention: Gene-based clopidogrel admin in Hmong and Dong PCI - Yuan, Xiangyi; Liu, Yang; Zhang, Teng; Xia, Jie; Lan, Xue; Pan, Qinxiang; Han, Minzhen (Cellular and Molecular Biology, 2024)
This study explored the distribution characteristics of CYP2C19 gene polymorphism among Hmong and Dong patients in the Qiandongnan region of Guizhou province after percutaneous coronary intervention (PCI). The aim was to assess the clinical impact of individualized clopidogrel administration based on CYP2C19 genotypes. A total of 208 patients were classified into ultra-fast, fast, intermediate, and slow metabolic groups. They were randomly assigned to clopidogrel individualized administration (IA) or conventional treatment (CA) groups. Patients were followed for 6 months to evaluate major adverse cardiovascular events (MACE) and adverse reactions. The CYP2C19 genotype distribution was in Hardy-Weinberg equilibrium, showing consistency in the population. While no significant ethnic differences were found in genotype and metabolic distribution, allele distribution varied, with Hmong patients exhibiting a higher proportion of CYP2C19*1 alleles than Dong patients. Following individualized administration, the IA group demonstrated lower incidences of non-fatal myocardial infarction and emergency revascularization compared to the CA group. Bleeding events were higher in the IA group, but the total MACE incidence was lower. No statistical difference in MACE and adverse drug reactions (ADR) was observed in the CA group across metabolic types, but MACE incidence was higher in intermediate and slow metabolic groups. In the IA group, no significant difference in MACE was noted among metabolic types, but ADR incidence varied significantly, particularly in dyspnea. The study highlighted significant CYP2C19 allele distribution differences between Hmong and Dong patients post-PCI in Qiandongnan. Patients with slow metabolic profiles demonstrated higher MACE incidence with conventional clopidogrel dosage, whereas CYP2C19-guided therapy reduced MACE without increasing bleeding risk. These findings supported clinical individualized clopidogrel administration in post-PCI patients in the Qiandongnan region, contributing to rational clopidogrel use.